2021
DOI: 10.1371/journal.pntd.0009266
|View full text |Cite|
|
Sign up to set email alerts
|

Derivation of the first clinical diagnostic models for dehydration severity in patients over five years with acute diarrhea

Abstract: Diarrheal diseases lead to an estimated 1.3 million deaths each year, with the majority of those deaths occurring in patients over five years of age. As the severity of diarrheal disease can vary widely, accurately assessing dehydration status remains the most critical step in acute diarrhea management. The objective of this study is to empirically derive clinical diagnostic models for assessing dehydration severity in patients over five years with acute diarrhea in low resource settings. We enrolled a random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Both studies have developed clinical diagnostic models for assessing dehydration severity from acute diarrhea using an ordinal outcome (none, some, or severe dehydration). The ordinal logistic regression models for the DHAKA study have undergone both derivation with internal validation and external validation, while the NIRUDAK study has undergone diagnostic model derivation with internal validation, and has planned external validation in 2022 [ 15 – 17 ]. Neither study has reported a predictive model for the amount of fluid deficit measured on a continuous scale.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both studies have developed clinical diagnostic models for assessing dehydration severity from acute diarrhea using an ordinal outcome (none, some, or severe dehydration). The ordinal logistic regression models for the DHAKA study have undergone both derivation with internal validation and external validation, while the NIRUDAK study has undergone diagnostic model derivation with internal validation, and has planned external validation in 2022 [ 15 – 17 ]. Neither study has reported a predictive model for the amount of fluid deficit measured on a continuous scale.…”
Section: Methodsmentioning
confidence: 99%
“…The models developed in this paper are secondary analyses of the DHAKA and NIRUDAK datasets; sample sizes for each dataset were calculated, a priori, for use as clinical diagnostic models [ 15 – 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected from the "Novel, Innovative Research for Understanding Dehydration in Adults and Kids" (NIRUDAK) study, a prospective cohort study of patients over 5 years of age presenting with acute diarrhea to the short-stay rehydration unit at the International Center for Diarrheal Disease Research, Bangladesh (icddr,b)'s Dhaka Hospital between March 2019 and March 2020. 20 Ethical approval for the NIRUDAK study was obtained from the icddr,b and Rhode Island Hospital Institutional Review Boards (IRBs).…”
Section: Methodsmentioning
confidence: 99%